In Dialogue with the Gospel - Ideström, Jonas (Ecclesial practices, 2014)
The aim of this article is to reflect on an approach and method for practical and prophetic ecclesiology. The article describes the process of planning and using a method at a conference for Church of Sweden suburban parishes. By returning to the conference and the planning process, the account presents the various steps of the broader approach, spells out ecclesiological considerations and analyses results of the conference. Gordon Lathrop’s concept, dialogue of holy things, is used to argue for the relevance of using a method based on Gospel narratives in empirical ecclesiology. The results from the conference show that the method could contribute to constructive and critical reflections on theological challenges facing Church of Sweden. The approach is discussed in relation to Theological Action Research and theories developed by Geir Afdal concerning studies of social practices.